Rice bran as source of nutraceuticals for management of cardiovascular diseases, cardio-renal syndrome and hepatic cancer - Sahar Y. Al-Okbi; Doha A. Mohamed; Thanaa E. Hamed; Enas S.K. Al-Siedy (Shahrekord University of Medical Sciences, 2020)
Introduction: The interrelation between cardiovascular diseases (CVDs) and renal dysfunction and the beneficial role of nutraceuticals are worthy to be studied. Nutraceuticals with anticancer effects are gaining great importance. The aim of this research was studying the anti-cancer, CVDs prevention and renal dysfunction properties of γ-oryzanol (γ-O) and rice bran oil/γ-O mixture (RBO/γ-O) as nutraceuticals. Methods: Rats were divided into 7 groups. Group 1 was fed on balanced diet and served as normal control (NC). Group 2 consumed high-fat-sucrose diet (HFSD) as CVD control. Groups 3 and 4 were fed on HFSD and treated by γ-O and RBO/γ-O, respectively. Group 5 was maintained on HFSD with cisplatin injection (cardiorenal syndrome control) (CRSC). Groups 6 and 7 were treated like group 5 and given either γ-O or RBO/γ-O. Plasma lipid profile, malondialdehyde (MDA), tumor necrosis factor-α (TNF-α), catalase activity, creatinine and urea were determined besides urinary creatinine clearance. Nutraceuticals' anticancer effect was assessed in hepatocellular carcinoma cell (HepG2) line. Results: Significant increases (P < 0.05) in lipid parameters with reduction of high-density lipoprotein cholesterol (HDL-C) were noticed in CVD control compared to NC group; the same changes were demonstrated in CRSC with lesser extent. In CVD control and CRSC groups; a significant increase (P < 0.05) in MDA and TNF-α with a reduction in catalase were noticed. Kidney dysfunction was demonstrated in the CRSC group. Administration of both RBO/γ-O and γ-O produced variable improvements in all parameters in both models and had anticancer effects. Conclusion: RBO/ γ-O and γ-O had protective effects on CVDs and cardiorenal syndrome as well as anti-hepatocellular carcinoma activities with superiority of RBO/γ-O.